Pierre Boulez - Jameux, Dominique 1939-2015 (Paris Fayard Fondation SACEM, 1984)
Dominique Jameux's study of Pierre Boulez appeared in 1984, with a second edition in 1986, and was translated into English in 1991. While the book necessarily stops before some interesting things happened in Boulez's career, such as the revival of "...explosante-fixe..." and the completion of "Repons", it is one of the most detailed overviews of his life and work up to that point. Part I, "Trajectoires" is the biographical portion of Jameux's work. It traces Boulez's life from birth through his youthful Paris iconoclasm, his groundbreaking works of the 1950s, the beginning of his conducting career in the 1960s, and finally the IRCAM era. Throughout Boulez is shown as a thoroughly fascinating man, a titan of his age, although Jameux isn't afraid to thrown in some criticism of his attitude.The second part, "Inscriptions", is a series of musicological analyses of twelve works. These are "Sonatine", the three piano sonatas, "Le Soleil des eaux", "Structures" (but only Book I), "Le Marteau sans maitre", "Pli selon pli" (in a shorter version than what is played nowadays), "Eclat" and "Eclat/Multiples", "Domains", "Rituel", and "Repons".
"Catalogue des œuvres": p. [447]-452.
Includes indexes.
Bibliography: p. [475]-478.
Discography: p. [453]-470.
Filmography: p. [471]-473.
Keywords: Boulez, Pierre -- 1925-2016; 20th Century (1901-2000); 21st Century (2001-2100); Composer; Conductor; Biography; Avant-garde; France